2021
DOI: 10.3390/brainsci11121632
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationships of P3b with Negative Symptoms and Neurocognition in Subjects with Chronic Schizophrenia

Abstract: Neurocognitive deficits and negative symptoms (NS) have a pivotal role in subjects with schizophrenia (SCZ) due to their impact on patients’ functioning in everyday life and their influence on goal-directed behavior and decision-making. P3b is considered an optimal electrophysiological candidate biomarker of neurocognitive impairment for its association with the allocation of attentional resources to task-relevant stimuli, an important factor for efficient decision-making, as well as for motivation-related pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 152 publications
(219 reference statements)
4
6
0
Order By: Relevance
“…Earlier studies did not report a relationship between cognitive P300 latency and negative symptoms. 68,69 These previous results also support the current notion. Yet, for a better understanding of the result of the current study, future research that employed motivational tasks is needed.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies did not report a relationship between cognitive P300 latency and negative symptoms. 68,69 These previous results also support the current notion. Yet, for a better understanding of the result of the current study, future research that employed motivational tasks is needed.…”
Section: Discussionsupporting
confidence: 91%
“…The resulting combination of EEG alterations, in chronic patients with schizophrenia, was associated with real-life functioning and with illness-related variables which have an impact on functional outcomes, such as cognitive impairment, depression, and negative symptoms, at 4-year follow-up [4,6]. Previous research identified alterations of several EEG indices in SCZs, which are related to different brain functions and associated with different illness features influencing the outcome or with the outcome itself [25][26][27][28][29]. However, despite the results of these studies, no EEG index has been implemented in clinical practice.…”
Section: Discussionmentioning
confidence: 96%
“…Several quantitative resting-state EEG and event-related potentials (ERP) alterations have been reported in SCZs in different stages of the illness and many of them are associated with psychopathology, cognitive impairment, and functional outcome [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to obtain a clearer view on the results, we also need to consider that several factors might have influenced or biased the correlations reported. Few studies, in fact, have considered the possible confounding effects of illness duration, antipsychotic doses and severity of psychopathological aspects on the outcomes [ 63 , 79 ]. Furthermore, physiological processes such as ageing have also often been associated with a progressing deterioration of P300 and MMN elicitation [ 279 , 280 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have also shown the presence of abnormalities in electroencephalographic (EEG) indices when subjects with schizophrenia-spectrum disorders and healthy controls were compared [ 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ]. EEG recordings, due to their high temporal resolution, have been vastly employed to characterize the complex cascade of neuronal signalling underlying cognitive processing and to detect which steps of this processing might be impaired in subjects with severe mental health disorders [ 57 ].…”
Section: Introductionmentioning
confidence: 99%